Chromosomal dif sites and associated modules identified in Acinetobacter sp. drive the horizontal transfer of antibiotic resistance - Wang, Qing; Wang, Weiwei; Qiu, Yanhua; Dai, Guonian; Li, Bing; Zhou, Yaxin; Bai, Yubin; Zhang, Jiyu (Frontiers in Microbiology, 2026)
IntroductionModules containing antibiotic resistance genes (ARGs) flanked by Xer site-specific recombination sites have been identified in Acinetobacter plasmids and are considered mobile genetic elements (MGEs) that facilitate horizontal gene transfer via the XerCD site-specific recombination (XerCD SSR) system. Although additional dif-like sites have been identified on the Acinetobacter chromosome beyond the main locus, it remains unclear whether these sites are associated with chromosomal dif modules.MethodsMacConkey agar plates supplemented with meropenem were used to isolate the resistant strain. Whole-genome sequencing (WGS) was performed on the Oxford Nanopore platform, and the bacterial species was identified using Average Nucleotide Identity (ANI) and digital DNA-DNA hybridization (dDDH). Antimicrobial susceptibility testing was performed against 18 antibiotics. Identification of dif and pdif sites was performed using BLAST tools.ResultsThis study identified numerous Xer modules containing resistance genes, IS elements, and other functional genes within the chromosome and plasmid of strain M10 (Acinetobacter sp.) isolated from a farmer at a cattle farm in Guangxi, China. Genome analysis and antimicrobial susceptibility testing confirm the association between these modules carrying resistance genes and resistant phenotypes. Chromosomal dif sites and associated dif modules in the strain were highly similar (sequence identity >99%) to plasmid-carried pdif sites and associated pdif modules in the public database. These suggest that additional chromosomal dif-like sites facilitate dif module formation, and that gene flow occurs between the chromosomes and plasmids of Acinetobacter. Furthermore, most Xer sites clustered to form a linear multi-module array, termed chromosomal dif module island and plasmid-borne pdif module island. Similar configurations were frequently observed in public Acinetobacter plasmid genomes.DiscussionAdditional dif-like sites are present in Acinetobacter chromosomes, which are unlikely to play a function in chromosomal dimer resolution, and the modules they form are functionally similar to pdif modules, both of which play an important role in horizontal gene transfer.